2018
DOI: 10.17826/cumj.423848
|View full text |Cite
|
Sign up to set email alerts
|

Serebral palsili çocuklarda spastisitenin myotonometri ile değerlendirilmesi ve spastisitede elektrik stimulasyonun etkinliği

Abstract: ÖzPurpose: The aim of this study was to evaluate the biomechenical properties (tone, elasticity, stifness) of gastrocnemius muscle (GCM) using myotonometry in children with spastic cerebral palsy (CP) and to demonstrate therapeutic effectiveness of electrical stimulation onmuscle tone, elasticity and stiffness. Materials and Methods: Forty patients with spastic CP (11 diplegic, 16 quadriplegic, 13 hemiplegic) and 20 age, gender and body mass index matched healthy controls were evaluated. MyotonPro was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the GM muscle, while elasticity was similar between the two groups, tone and stiffness showed worse results in the CP group. In our study, when we looked at the GM and GL measurement results in the hemophilia group, tone was higher and elasticity was lower, but there were no significant differences between the groups [17]. Hemarthroses occur in the knee in 60% of patients with hemophilia, affecting the biomechanical alignment of the lower extremity [27].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the GM muscle, while elasticity was similar between the two groups, tone and stiffness showed worse results in the CP group. In our study, when we looked at the GM and GL measurement results in the hemophilia group, tone was higher and elasticity was lower, but there were no significant differences between the groups [17]. Hemarthroses occur in the knee in 60% of patients with hemophilia, affecting the biomechanical alignment of the lower extremity [27].…”
Section: Discussionmentioning
confidence: 64%
“…MyotonPRO has been used to evaluate mechanical properties in healthy individuals [12], athletes [13], and geriatric individuals [14], and various diseases [15,16]. However, in the pediatric group, myotonometric measurements are frequently preferred in diseases such as cerebral palsy, brachial plexus injury, and in children with developmental delays [17][18][19][20]. To date, no study has been found to investigate the changes in the viscoelastic properties of the lower-extremity muscles in pediatric hemophilia patients.…”
Section: Introductionmentioning
confidence: 99%